Different Modes of Gene Duplication Show Divergent Evolutionary Patterns and Contribute Differently to the Expansion of Gene Families Involved in Important Fruit Traits in Pear (Pyrus bretschneideri) - Qiao, Xin; Yin, Hao; Li, Leiting; Wang, Runze; Wu, Juyou; Wu, Jun; Zhang, Shaoling (Frontiers in Plant Science, 2018)
Pear is an important fruit crop of the Rosaceae family and has experienced two rounds of ancient whole-genome duplications (WGDs). However, whether different types of gene duplications evolved differently after duplication remains unclear in the pear genome. In this study, we identified the different modes of gene duplication in pear. Duplicate genes derived from WGD, tandem, proximal, retrotransposed, DNA-based transposed or dispersed duplications differ in genomic distribution, gene features, selection pressure, expression divergence, regulatory divergence and biological roles. Widespread sequence, expression and regulatory divergence have occurred between duplicate genes over the 30-45 million years of evolution after the recent genome duplication in pear. The retrotransposed genes show relatively higher expression and regulatory divergence than other gene duplication modes. In contrast, WGD genes underwent a slower sequence divergence and may be influenced by abundant gene conversion events. Moreover, the different classes of duplicate genes exhibited biased functional roles. We also investigated the evolution and expansion patterns of the gene families involved in sugar and organic acid metabolism pathways, which are closely related to the fruit quality and taste in pear. Single-gene duplications largely account for the extensive expansion of gene families involved in the sorbitol metabolism pathway in pear. Gene family expansion was also detected in the sucrose metabolism pathway and tricarboxylic acid cycle pathways. Thus, this study provides insights into the evolutionary fates of duplicated genes.